2016
DOI: 10.1038/srep32136
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Controls on Water Adsorption and Condensation Regimes at Mineral Surfaces

Abstract: Atmospheric water vapour interacting with hydrophilic mineral surfaces can produce water films of various thicknesses and structures. In this work we show that mineral particle size controls water loadings achieved by water vapour deposition on 21 contrasting mineral samples exposed to atmospheres of up to ~16 Torr water (70% relative humidity at 25 °C). Submicrometer-sized particles hosted up to ~5 monolayers of water, while micrometer-sized particles up to several thousand monolayers. All films exhibited vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 62 publications
8
76
10
Order By: Relevance
“…Such processes are closely related to the particle size of the mineral substrate. Recently, it has been stated that in particular, micron-sized particles (with a specific surface area of less than~10 m 2 /g) should tend to be more capable of promoting such water condensation than submicron-sized particles [31].…”
Section: Discussionmentioning
confidence: 99%
“…Such processes are closely related to the particle size of the mineral substrate. Recently, it has been stated that in particular, micron-sized particles (with a specific surface area of less than~10 m 2 /g) should tend to be more capable of promoting such water condensation than submicron-sized particles [31].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary minerals under rock‐dominated conditions (Table ) formed by condensation of liquid water on the micronized basalt allowing aqueous mineral dissolution‐precipitation processes at very low water:rock ratios (Yeşilbaş and Boily ). The observed mineralogy in rock‐ and fluid‐dominated conditions was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that particle size controls the condensation of water and the formation of water films (Yeşilbaş & Boily, ). How the thickness of the water film, interactions between the soil particle surface, mobile, immobile water, and water vapour combine to control the isotopic environment is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%